Screen-printed immunosensor for quantification of human serum IgG antibodies to Helicobacter pylori - Messina, Germán Alejandro (2007)
This paper describes the development of a screen-printed immunosensor for the rapid and sensitive quantification of human serum immunoglobulin G (IgG) antibodies to Helicobacter pylori. This microorganism cause peptic ulcers and chronic gastritis, affecting around the 10% of the world population. Antibodies in the serum sample are allowed to react immunologically with the purified H. pylori antigens that are immobilized on graphite screen-printed electrodes (GSPE). The bound antibodies are quantified by alkaline phosphatase (AP) enzyme-labeled second antibodies specific to human IgG. p-Aminophenyl phosphate (p-APP) was converted to p-aminophenol (p-AP) by AP, and an electroactive product was quantified using Osteryoung square wave voltammetry (OSWV). The electrochemical detection can be done within 1 min and total assay time was 25 min. The calculated detection limits for electrochemical detection and the ELISA procedure are 0.5 and 1.8 U ml-1, respectively. Reproducibility assays were made using repetitive standards of H. pylori specific antibody (measured as the activity of the correspondent anti-serum's enzyme conjugated) and the intra- and inter-assay coefficients of variation were below 5%. The electrochemical immunosensor showed higher sensitivity and lower time consumed than the standard spectrophotometric detection ELISA method, demonstrate its potential usefulness for early assessment of human serum immunoglobulin G (IgG) antibodies to H. pylori. © 2007 Elsevier B.V. All rights reserved.